Comparison of microwave-assissted hydrodistillation with the conventional hydrodistillation method in the extraction of essential oil. - Hanis Farzana, Mohd Sadek (2010)
The production of essential oils from natural sources is highly profitable nowadays.People worldwide start to realize the important of healthy awareness.Highly demand of ginger (Zingiber officinale Roscoe) oil and citronella grass (Cymbopogon nardus) oil due to its uses.Here,a modern and an alternative method,microwave-assisted hydrodistillation (MAHD is approach.The purpose of this study is to investigate the performance of MAHD on the extraction of essential oils.The essential oils from ginger and citronella grass were studied and results were compared with the conventional HD in terms of extraction yield,extraction time,cost of operation and chemical composition.MAHD was provided higher quantitative in short of time.MAHD resulted in similar citronella oil recovery for 60 min to that obtained by 90 min of HD (1.17%, v/w).Same as ginger essential oil,MAHD required extraction time period of 30 min for recovering 0.88% yield of essential oil of ginger, instead of HD required 90 min of extraction time for recovering same percentage yield.Gas chromatography-mass spectrometry analysis of the extracted essential oils indicated that the use of microwave irradiation recover high total peak area (%).MAHD was found to be a green technology.